The Issue of Maritime Connectivity and Peripherality in the Adriatic - E. A. Maslova (Международная аналитика)
The Adriatic Sea, as part of the Mediterranean Sea, plays an important role in the regional and international maritime connected system. Historically, it served as an important trade route, connecting Europe to the East, thanks to the power of the Republic of Venice. Today, the Mediterranean is one of the busiest waterways in Europe, but the main traffic transits to the North Sea – to the ports of Rotterdam, Antwerp, and Hamburg. In the modern context, there is a perception of this sea as “peripheral“ due to its geographical location and limited access to the world’s shipping routes. The geographical configuration of the Adriatic Sea as a part bordering the continental landmass and partly surrounded by peninsulas or archipelagos makes this sea de facto naturally enclosed and located far away from the main global shipping routes.The main vector of traffic in the Adriatic is from North to South, with ports orientated towards access to the greater Mediterranean Sea and the delivery of cargo from non-EU countries. The Adriatic is a strategically important region (Adriatic-Ionian macro-region) for the European Union. The EU initiates strategies and promotes projects to improve maritime connectivity and strengthen regional links. The development of pan-European TEN-T transport corridors opens new perspectives for improving maritime connectivity and competitiveness of ports in the northern Adriatic, such as Venice, Koper, Trieste, Ravenna, Rijeka. These ports are becoming an alternative to the traditional Northern European ports of Hamburg – Le Havre, aiming to occupy key positions in the European logistics chain. To a large extent, this competitiveness is ensured, on the one hand, by the development of ‘hinterland’ and, on the other hand, by intermodal transport. Significant challenges remain to modernising infrastructure, improving conditions for intermodal transport, and overcoming the historical legacy of being “peripheral.” The overarching goal of the ports of the northern Adriatic is to become a multiport hub. However, apart from the geographical factor, the competitiveness of the Adriatic ports is increasingly determined by geopolitics and instability – the Houthi attacks are provoking a reduction in shipping traffic in the Suez Canal, which will inevitably affect the demand for Northern Adriatic ports.